Development of 58-Tooth chainring for time trial stages (2024)
This project aimed to develop an affordable bicycle chainring for cyclists specialized in time trials, starting without any existing foundation. A comprehensive process was undertaken, encompassing concept generation, concept selection, and reliability testing through simulation. Once the optimal concept was chosen, a detailed simulation was performed to ensure its compliance with client requirements, after confirming the concept's effectiveness through simulation, the preselected material, aluminum 7075-T6, widely used in the cycling sector, was procured. A base to facilitate manufacturing was machined, followed by the CNC machining of the aluminum material. The resulting product visually met the expected standard to ensure the chainring's performance, rigorous tests were conducted, demonstrating outstanding compliance with the proposed indicators. This process establishes a solid foundation for a potential project continuation, emphasizing the successful material selection, design efficiency, and the achievement of a product meeting the needs and expectations of time trial cyclists.